Field performance of different maize varieties in growth cores at natural and reduced mycorrhizal colonization: yield gains and possible fertilizer savings in relation to phosphorus application - Wang, Xin-Xin; van der Werf, Wopke; Yu, Yang; Hoffland, Ellis; Feng, Gu; Kuyper, Thomas W. (Plant and soil, 2020)
Aims The benefits of arbuscular mycorrhizal fungi (AMF) on yield and phosphorus (P) uptake of crops have commonly been studied by inoculating a single mycorrhizal fungal species in pot experiments. Yet, how the native AMF community affects the performance of different maize varieties under field conditions remains obscure. Methods In-growth cores with and without rotation were used in three soils that differed in P application to assess shoot biomass, P uptake, and mycorrhizal colonization of three maize varietal groups, encompassing four inbred lines, 12 hybrids, and four landraces. Results Rotating cores drastically reduced mycorrhizal colonization, biomass and P uptake for each varietal group at every P level. Performance of plants at natural mycorrhizal colonization at 30 kg P ha −1 was equal to that of reduced-mycorrhizal plants at 60 kg P ha −1 , suggesting the potential for adequate mycorrhizal management to save P fertilizer. Conclusion There were no significant differences between varietal groups for mycorrhizal responsiveness, confirming that the ability to associate with and benefit from AMF has been maintained in modern breeding. Mycorrhizal plants both exhibited higher P acquisition efficiency and higher P use efficiency than reduced-mycorrhizal plants. Disadvantages of in-growth cores should be duly considered.